Characterization of Nash Equilibrium Strategy of a Two Person Non Zero Sum Games with Trapezoidal Fuzzy Payoffs - kumari, K. Selva (International Journal of Psychosocial Rehabilitation, 2020)
In this article, we have considered the Bimatrix game with symmetric trapezoidal Pay-off’s and then we define Nash Equilibrium solution for pure and mixed strategies. We extended the models of investigating Nash Equilibrium strategy of a two person Non zero sum games with fuzzy payoff’s in trapezoidal fuzzy environment and also proposed the methodology for the existence of equilibrium strategies. In addition to that, numerical examples are presented to find Nash Equilibrium for the Bimatrix game.